Profile of pregnant adolescents in a small town in the countryside of Paraná - Oliveira, Beatriz Rosana Gonçalves de; Viera, Cláudia Silveira; Fonseca, Juliene Flávia Noris Almeida (Rev Rene, 2011)
This study aimed to identify the profile of pregnant adolescents, considering the influence of biological, psychological and social variables, in a small town in Paraná, to support prevention programs for teenage pregnancy. This is a quantitative study; the data obtained used structured interview with descriptive statistical analysis. The variables analyzed were: menarche age, gynecological age, age at childbirth, contraception use, family relationship, acceptance and planning of pregnancy, educational achievement, repetition and school exodus, family income, marital status, number of partners up to pregnancy and means of access to sexual education. The profile obtained showed that adolescents have early menarche, only one sexual partner, reducing the use of contraceptives, positive reaction of the family in relation to the current pregnancy, school failure and dropout, lack of gainful occupation and low household income. The survey showed information for the health staff of the municipality concerning the development of specific actions for the prevention of teenage pregnancy.